Woman Violence in â€œMimi Lan Mintunaâ€ novel written by Remy Sylado - Moon, Yuliana Jetia (STKIP Santu Paulus Ruteng, 2016)
This research attemptsto describle and analyze types of violence and the affecting factors revealed in woman charactersin the novel. It was designed in descriptive qualitative research method. The results of analysis indicatethat woman violence are of some types such as psychological and physical abuse, apparent and hiddenviolence, personal and structural harrassment as well as situational maltreatment. With regard to violence,there are two leading factors, namely internal and external factors.